Performance Analysis of Using the Next generation Australian SBAS with Precise Point Positioning Capability for Intelligent Transport Systems - El-Mowafy, Ahmed; Cheung, N.; Rubinov, E. (2019)
© 2019 IEEE. In 2018, a next-generation Satellite-Based Augmentation System (SBAS) test-bed was launched in Australia/New-Zealand in preparation for building an operational system. This new generation SBAS includes Ll legacy SBAS, new dual-frequency multi-constellation (DFMC) SBAS, and orbit and clock corrections for precise point positioning (PPP) using GPS and Galileo. In this paper, the next generation SBAS and its models are first presented, and the benefits of using its new components are discussed. Test results for lane identification applications in Intelligent Transport Systems (ITS) are presented and analyzed. Kinematic tests were performed in different ITS environments. These are characterized by different levels of sky-visibility and multipath, including clear sky, suburban, low-density urban, and high-density urban environments. Performance analysis show that results vary widely depending on the operational conditions but all SBAS solutions have better positioning accuracy compared with the standalone solutions that are currently used in transport applications. The DFMC SBAS slightly outperformed the Ll SBAS, with accuracy at sub-meter, and it has advantages during periods of fluctuations of the ionosphere with an extended coverage area. As expected, the SBAS-based PPP solutions have shown to give the best positioning precision and accuracy among all tested solution types, with sub-decimeter level accuracy, provided that enough convergence time is available. The paper concluded by giving remarks on the use of this new technology for ITS.